ZAKAT PROFESI (PERSPEKTIF FIQH KLASIK DAN KONTEMPORER) - Nazaruddin A Wahid; Hamdani Hamdani (Sekolah Tinggi Ilmu Ekonomi Syariah Baktiya Aceh Utara, 2021)
ABSTRACT Classical jurisprudence has established obligatory zakat on the salaries of soldiers, the salaries of judges and the rewards of the profession of Madalim officers (lawyers) which have been practiced by Ibn Mas'ud, Mu'awiyah ibn Abi Sofyan and Umar ibn Abdul Aziz. Contemporary fiqh only extends this concept to a situation that is relevant to the change of profession that is being struggled between the situation in the early days of Islam and the present. However, it is acknowledged that there are certain sects that do not mention the zakat of the profession such as the Malikiyah and Syafiíyah groups. There is no qath'i text, either in the Qur'an or in the Sunnah about the nisab of zakat of the profession, therefore the determination of nisab is done by using qiyas and scholars agree to rely on the nisab of zakat harta. Some other scholars, compare it to zakat zuru ', and naqdin. The Indonesian Muslim community is based on zakat naqdin, so that the nisab is equated with 20 dinars or 200 dirhams with the current dose of 85 grams of pure gold and the zakat rate of 2.5 %. Regarding who has the right to collect zakat, including professional zakat, there is no difference between classical fiqh and contemporary fiqh, who has the right to collect and collect zakat is the government, in practice partnering with specialized institutions. Similarly, the utilization of zakat, can be done productively and consumptively with consideration of the basis of the greater benefits received by the mustahik. ABSTRAK Fiqh klasik telah menetapkan wajib zakat terhadap gaji tentara, gaji Hakim dan imbalan profesi petugas Madalim (pengacara) yang telah diprakteekkan oleh Ibnu Mas’ud, Mu’awiyah bin Abi Sofyan dan Umar bin Abdul Aziz. Fiqh kontemporer hanyalah mengembangkan konsep ini kepada keadaan yang relevan dengan perubahan profesi yang digeluti antara keadaan pada masa awal Islam dengan masa sekarang. Namun diakui ada golongan mazhab tertentu yang tidak menukilkan mengenai zakat profesi seperti golongan Malikiyah dan Syafiíyah. Tidak ada nas yang qath’i, baik dalam al-Quran maupun dalam al-Sunnah tentang nisab zakat profesi, karenanya penetapan nisab dilakukan dengan menggunakan qiyas dan sepakat ulama menyandarkan kepada nisab zakat harta. Sebagian ulama lain, mengqiyaskan kepada zakat zuru’, dan naqdin. Masyarakat muslim Indonesia mendasarkan zakat naqdin, sehingga nisabnya disamakan dengan 20 dinar atau 200 dirham dengan takaran sekarang 85 gram emas murni dan kadar zakatnya 2,5 %. Mengenai siapa yang berhak mengumpulkan zakat, termasuk zakat profesi, tidak ada perbedaan antara fiqh klasik dan fiqh kontemporer, yang berhak memungut dan mengumpulkan zakat adalah pemerintah, dalam praktiknya bermitra dengan lembaga khusus. Demikian juga tentang pemanfaatan zakat, dapat dilakukan secara produktif dan konsumtif dengan pertimbangan asas manfaat lebih besar diterima oleh mustahik. Kata Kunci: Zakat profesi, Fqh klasik, Fiqh kontemporer